2000
DOI: 10.1021/jp9944280
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of Molecular Diffusion and Dynamic Flow through Carbon Nanotubes

Abstract: Molecular dynamics simulations are used to study the flow of methane, ethane, and ethylene through carbon nanotubes at room temperature. The interatomic forces in the simulations are calculated using a classical, reactive, empirical bond-order hydrocarbon potential coupled to Lennard-Jones potentials. The simulations show that the intermolecular and molecule-nanotube interactions strongly affect both dynamic molecular flow and molecular diffusion. For example, molecules with initial hyperthermal velocities slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
173
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(180 citation statements)
references
References 47 publications
7
173
0
Order By: Relevance
“…Beckstein et al [3,4] have extended such simulations to 2 study the density fluctuations of water inside other hydrophobic pores. Transport of oxygen and organic molecules such as methane, ethane and ethylene through carbon nanotubes has also been studied [13,14,15,16] through MD simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beckstein et al [3,4] have extended such simulations to 2 study the density fluctuations of water inside other hydrophobic pores. Transport of oxygen and organic molecules such as methane, ethane and ethylene through carbon nanotubes has also been studied [13,14,15,16] through MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The simulations of Mao et al [14] suggest that spherical methane molecules exhibit normal mode diffusion inside closed carbon nanotubes, whereas aspherical molecules such as ethane and ethylene diffuse by a mode which is between normal and single-file. In all these simulations, the time over which the MSD is measured is rather short (100 − 500 ps).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore not comparable to our work. Sinnott and co-workers [29][30][31][32] simulated the carbon nanotube as a flexible framework. They studied entrance effects, transport diffusion, and molecular diffusion for various carbon nanotubes and various guest molecules.…”
Section: Introductionmentioning
confidence: 99%
“…While this simplifies the simulation considerably, our previous work has demonstrated that molecular shape can have a significant influence on molecular diffusion through nanopores [6]. Therefore the approach that is being taken is one where the atoms are treated explicitly and the molecules are characterized with Coulomb and Lennard-Jones (LJ) potentials [7,8].…”
Section: Separation Of Flowing Stream Of Co 2 and N 2 On Packed Mwnt Bedmentioning
confidence: 99%